An investigation of factors influencing antimicrobial resistance in dairy herds - McLaughlin, Daniel (2023)
The emergence of antimicrobial resistance (AMR) as a result of the selective pressures placed on both commensal and pathogenic bacterial populations as a result of overuse and misuse of antimicrobials is one of the greatest issues facing human healthcare. Antimicrobials are widely used in agriculture for the maintenance of health and welfare, but their use also contributes to the issue of AMR and poses a risk to human health via the food chain. In order to tackle the challenge, governments and organisations across the world have committed to reducing antimicrobial use (AMU) in agriculture and to implement surveillance programmes to monitor AMR. Although AMU in agriculture in the United Kingdom (UK) is reducing, there remains a knowledge gap regarding the dynamics which exist in terms of AMU/AMR associations and the influences of the wider farm environment.